Three Vital Questions for Mega Planning and Two Possible Approaches to Answering them Appropriately. Issue 6 (21st May 2018) - Kaufman, Roger; Addison, Roger; Kearny, Lynn
Abstract: To identify and resolve important problems, it is critical to ask and answer basic questions. Three vital questions are suggested, and two paradigms are provided to best answer them and to define the value added by the two approaches.